Development of Adjustment Factors affecting The Capacity of DRR Two-Lane Highways with Indirect Empirical Method - chaipanha, wuttikrai (Srinakharinwirot University Engineering Journal, 2020)
The objective of this study is to develop the adjustment factor for use in estimating capacity of DRR two-lane highways by using the development of traffic micro-simulation model instead of directly observed, as well as presenting the impact of factors affecting the capacity of the DRR two-lane highway. The results show that the estimation of the average maximum capacity of all 3 site is 3,671 pc/h, with the proportion of motorcycles being the factor that causes the maximum capacity to be reduced compared to the base condition due to the driving behavior with other vehicles on the carriageway. In this regard, the researcher has summarized the adjustment table of the proportion of motorcycle, proportion of heavy vehicle and directional split, as an alternative way to use the capacity estimation of DRR two-lane highways.